2015
DOI: 10.1038/srep12564
|View full text |Cite
|
Sign up to set email alerts
|

LK6/Mnk2a is a new kinase of alpha synuclein phosphorylation mediating neurodegeneration

Abstract: Parkinson’s disease (PD) is a movement disorder due to the loss of dopaminergic (DA) neurons in the substantia nigra. Alpha-synuclein phosphorylation and α-synuclein inclusion (Lewy body) become a main contributor, but little is known about their formation mechanism. Here we used protein expression profiling of PD to construct a model of their signalling network from drsophila to human and nominate major nodes that regulate PD development. We found in this network that LK6, a serine/threonine protein kinase, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
(62 reference statements)
0
15
1
Order By: Relevance
“…On the other hand, we found nuclear inclusions, which are excluded from the nucleoli. Despite sporadic reports of the occurrence of aSyn aggregates in the nuclei (58,59), the morphology we observe has not, to the best of our knowledge, been previously described. Nuclear inclusions are ubiquitinated and exclusively formed by endogenous aSyn, as recombinant species were not present in the nuclear compartment.…”
Section: Discussioncontrasting
confidence: 39%
“…On the other hand, we found nuclear inclusions, which are excluded from the nucleoli. Despite sporadic reports of the occurrence of aSyn aggregates in the nuclei (58,59), the morphology we observe has not, to the best of our knowledge, been previously described. Nuclear inclusions are ubiquitinated and exclusively formed by endogenous aSyn, as recombinant species were not present in the nuclear compartment.…”
Section: Discussioncontrasting
confidence: 39%
“…α-Syn is a soluble protein highly expressed presynaptically in neurons and can be found as an αhelical structure associated with phospholipids or in an unfolded conformation in the cytosol 3,4 Misfolded α-Syn forms oligomers and fibrils that are highly toxic to cells, and is the main component of Lewy Bodies, intracellular inclusions characteristic of PD which may promote neuroprotection through sequestration of toxic α-Syn fibrils, or directly contribute to neurotoxicity 4 . Although its physiological function remains not well understood, α-syn has been strongly implicated in synaptic plasticity and neurotransmitter release 5 . Mutations in alpha-synuclein were the first identified genetic cause of PD and subsequently a number of missense mutations, as well as gene duplications, have been observed in PD patients 2 Mitochondria undergo constant rounds of fission (mitochondrial division), or fusion.…”
Section: The Pd-associated Proteins Alpha-synuclein Pink1 Parkin Amentioning
confidence: 99%
“…Recent insights have shown that this protein may also act like a prion, propagating from one neuron to another, therefore enhancing brain degeneration 33,35,36 . Phosphorylation of α-syn at Ser-129 exacerbates the formation of α-syn inclusions, with over 90% of α-syn in LBs being phosphorylated at this residue, resulting in increased toxicity and neuronal death 5,23,27,34 . In a study by Karampetsou and colleagues (2017), α-syn was injected into mouse striatum in its wild type form versus its phosphorylated form, and they observed that phosphorylated α-syn demonstrated enhanced pathology in the SN compared to WT α-syn, increasing dopaminergic neuronal loss 27 .…”
Section: Ptms Of α-Synmentioning
confidence: 99%
See 1 more Smart Citation
“…The main component of the pathological lesions is extensively phosphorylated α-Syn at serine 129 (pS129 α-Syn)14, and pS129 α-Syn may play a critical role in synucleinopathy pathogenesis. Phosphorylation at Ser129 can regulate α-Syn fibril formation14151617 and enhance α-Syn toxicity both in vitro and in vivo 18192021. As the main form of α-Syn in the pathological process, pS129 α-Syn may be associated with multiple strain formation in vivo .…”
mentioning
confidence: 99%